On the Relative Strength of Double Fourier Series and its Allied Series - Gyan Das, S. K. Sahani, A. K. Thakur (Mathematical Statistician and Engineering Applications, 2021)
In this study, we have established four theorems concerning the generalizability of postponed Borel sums of double Fourier series. Our results are special examples of results achieved by others, such as the generalized Borel summability of double Fourie series and its linked series.